Sampling with a Rope - a Novel and Useful Method - Satyamurthi, K. B. (Indian Forester, 1979)
It is well known that the point sampling (Bitterlich method) using Relaskop or Wedge prism is quick and useful. But the method of enumeration assumes two important requirements. One is that all trees should be having perfect circular shape at breast height. Second one is the trees are assumed as trans parant entities. Obviously first assumptions on is not always true and the second one is false. Hence the estimate of basal area is not an anbiased one. Here we are going to relax these two assumptions and use only a rope instead oC Relascop or any other related instruments. The method ia simple and useful.